Quant'Os sertões: escritura e experiência literária em Os sertões, de Euclides da Cunha - Cesar Goncalves de Oliveira (2009)
This dissertation discusses literary readings of the War of Canudos, some texts published before 1902 and, more specifically, on the various possibilities of reading the book Os sertões, of Euclides da Cunha, due to its hybrid nature, between science and literature, common the genres of travel reporting and essay, and the encyclopedic project, to include multiple knowledge in various speeches. All this in a work that doesnot lack style, aesthetic and elements of poetic. For both, we use different theoretical concepts, among which the travel reporting, the essay as experiment thinking, the encyclopedic project and the writing, and try to systematize the concept of literary experience, dispersed in several texts. We try demonstrate the contributions of Os sertões in thought and mainly in the national imagination, since founded a new line of interpretation of Brazil.